Prolyl-tRNA synthetase from Thermus thermophilus is eukaryotic-like but aminoacylates prokaryotic tRNAPro - Yaremchuk, A.D.; Boyarshin, K.S.; Tukalo, M.A. (Вiopolymers and Cell, 2012)
Aim. Cloning, sequencing and expression of the gene encoding prolyl-tRNA synthetase, a class IIa enzyme, from the extreme thermophile T. thermophilus HB8 (ProRSTT). Methods. Search for the ProRSTT gene was performed by Southern blot hybridization with chromosomal DNA, the digoxigenin-labeled PCR fragments of DNA being used as a probe. Results. The gene of T. thermophilus HB8 ProRS has been cloned and sequenced. The predicted 477-amino acid protein is significantly more similar in sequence to eukaryotic and archaeal than to eubacterial ProRS. Sequence analysis shows two distinct structural groups of ProRS which most likely had diverged early in evolution: (1) eukaryotic/archaeal group characterized by the absence of an insertion domain between motifs 2 and 3 and by the presence of an extra C-terminal domain beyond the normal class IIa anticodon binding domain; and (2) prokaryotic with a very large insertion between motif 2 and 3 and no extra C-terminal domain. Conclusions. T. thermophilus proS gene was overexpressed in Escherichia coli and overproduced ProRSTT was purified to high homogeneity. In spite of its eukaryotic-like features, T. thermophilus ProRS exhibited highly specific cross-species aminoacylation. The charging ability of the ProRSTT is restricted to prokaryotic tRNAPro. Keywords: prolyl-tRNA synthetase from Thermus thermophilus, proS gene, сloning, sequencing, expression.